Effect of ground copper slag on the fresh properties of 3d printed cementitious composites - Martyna Nieświec; Adrian Chajec; Branko Šavija (Scientific Reports)
Abstract 3D printing is becoming increasingly popular in the construction sector. 3D printing offers the potential to reduce costs, construction time and construction waste. However, due to its high cement content, 3D printable concrete more expensive to produce. The article includes a brief literature survey on the possibility of using cement and aggregate substitutes in concrete mixtures and their impact on fresh composite properties and identifies a research gap. Herein, we propose the use of waste copper slag as a replacement for cement in 3D printable concrete. We examine the effect of replacing cement with copper slag at 5 and 10% on fresh properties of cementitious mortar. The results show that copper slag improves the workability of the mixture and lowers the design yield strength up to 44%, thereby facilitating printing. Even 30% higher fresh compressive strengths were also obtained, which suggest that the buildability of mortars containing copper slag will be improved.